2011
DOI: 10.1007/s10404-011-0921-3
|View full text |Cite
|
Sign up to set email alerts
|

Droplet transportation using a pre-charging method for digital microfluidics

Abstract: A new droplet-driving scheme for digital microfluidics termed the ''pre-charging of a droplet'' is demonstrated. In this method, a droplet is initially charged by applying ''pre-charging'' voltage between the droplet and an electrode buried under dielectric layers. The droplet is then driven to the next electrode by applying ''driving'' voltage between two adjacent buried electrodes. The concept of pre-charging was proved by the polarity of the charge stored in the droplet. When the droplet is precharged with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 23 publications
0
22
0
Order By: Relevance
“…The Faradaic charging of water droplets was also employed in digital microfluidic devices to manipulate water droplets above a system of microelectrodes. 13 Instead of the dielectric oil phase, the actuation electrodes were covered by a thin film of an insulator. More information about droplet handling in microfluidic devices can be found e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The Faradaic charging of water droplets was also employed in digital microfluidic devices to manipulate water droplets above a system of microelectrodes. 13 Instead of the dielectric oil phase, the actuation electrodes were covered by a thin film of an insulator. More information about droplet handling in microfluidic devices can be found e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Modeling of drop/particle motion experiencing the contact charging phenomenon is one of the key subjects in this field [4][5][6]66,[74][75][76][77][78][79][80][81][82]. In microfluidics field, the direct contact charging is used to manipulate droplet [38,[83][84][85][86] or particle motions [20,75] in microchannels in addition to digital microfluidic approaches [6,23,70,77,[87][88][89]. The details of each category will be covered in the following fundamentals and applications section.…”
Section: Historymentioning
confidence: 99%
“…They showed some potentials for the ECD as a digital microfluidic actuation method; however, in their work, the system size was too large and the actuation voltage was too high (few kilovolts), which limited the applicability of the technology. For that reason, there is a preconception that a high actuation voltage on the order of kilovolts is required for ECD actuation [87], which is not the case for smaller systems [6]. Later, Im et al resolved this issue by decreasing system size and demonstrated various biochemical applications such as hydrogel and crystal formation as shown in Fig.…”
Section: Fundamentals and Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Choi et al recently presented a droplet manipulation technique, whereby a water droplet is given a charge from an electrode and is then driven by electric fields (Choi et al, 2012). Apart from carrying a native charge, water-in-oil droplets can also be deliberately charged through direct contact with a voltagebiased electrode (Khayari et al, 2003).…”
Section: Introductionmentioning
confidence: 99%